2005
DOI: 10.1073/pnas.0406056102
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evolutionary genetics of spontaneous mutations affecting fitness in rhabditid nematodes

Abstract: Deleterious mutations are of fundamental importance to all aspects of organismal biology. Evolutionary geneticists have expended tremendous effort to estimate the genome-wide rate of mutation and the effects of new mutations on fitness, but the degree to which genomic mutational properties vary within and between taxa is largely unknown, particularly in multicellular organisms. Beginning with two highly inbred strains from each of three species in the nematode family Rhabditidae (Caenorhabditis briggsae, Caeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
221
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(242 citation statements)
references
References 74 publications
17
221
4
Order By: Relevance
“…An ML analysis of the fitnesses of MA and control lines gave an estimate for the mean mutational effect on fitness of *20%, and suggested that the DEM for fitness is fairly platykurtic (Vassilieva et al 2000; Table 1). U was estimated to be only about 0.005 per haploid genome per generation, consistent with other spontaneous MA experiments in C. elegans (Keightley and Caballero 1997;Baer et al 2005). However, by direct DNA sequencing of samples of the genome from the MA lines, Denver et al (2004) estimated that about two mutation events per haploid genome per generation had occurred.…”
Section: Incorporating Information On Nucleotide Mutation Ratessupporting
confidence: 58%
“…An ML analysis of the fitnesses of MA and control lines gave an estimate for the mean mutational effect on fitness of *20%, and suggested that the DEM for fitness is fairly platykurtic (Vassilieva et al 2000; Table 1). U was estimated to be only about 0.005 per haploid genome per generation, consistent with other spontaneous MA experiments in C. elegans (Keightley and Caballero 1997;Baer et al 2005). However, by direct DNA sequencing of samples of the genome from the MA lines, Denver et al (2004) estimated that about two mutation events per haploid genome per generation had occurred.…”
Section: Incorporating Information On Nucleotide Mutation Ratessupporting
confidence: 58%
“…Fitness assays also follow Baer et al [11]; see electronic supplementary material, text S2. Fitness was assayed in two blocks; 30 MA lines from each strain/MA temperature were randomly selected for each block, along with ancestral controls.…”
Section: Materials and Methods (A) Mutation Accumulation And Fitness Amentioning
confidence: 99%
“…The MA protocol follows Baer et al [11]; see electronic supplementary material, text S1. We initiated two sets of 192 replicate MA lines from the N2 strain of C. elegans and from the PB800 strain of C. briggsae; 96 lines were kept at 188C and 96 at 268C.…”
Section: Materials and Methods (A) Mutation Accumulation And Fitness Amentioning
confidence: 99%
“…After nematodes were visibly gravid (but before they laid eggs) they were transferred individually to fresh, seeded NGM plates and incubated at 20°C for 24 h. After the 24 h, the adult nematodes were removed, and plates were incubated another 24 h at 20°C to allow hatching. Plates were stored at 4°C until stained and counted (Baer et al, 2005) for the purposes of confirming fitness category and to confirm that the assay successfully imposed stress (by definition, 'stressful' environments decrease fitness, Martin and Lenormand, 2006). We analyzed the proportion of nematodes on a plate that survived to Day 3, the first day in which gravid adult nematodes were found on any plate.…”
Section: Stress Assaysmentioning
confidence: 99%
“…The 10 starting stocks (generation 250) from the Matsuba et al (2012) second order MA experiment and the canonical Baer lab N2 ancestor (Baer et al, 2005) were acquired as live worms at the time that Matsuba et al conducted their fitness assay. All lines were cryopreserved using standard methods.…”
Section: Stocks and Assay Preparationmentioning
confidence: 99%